SATISFACTION OF INTERNATIONAL AND DOMESTIC TOURISTS IN MALAYSIA’S OLDEST NATIONAL PARK: TAMAN NEGARA PAHANG - Chew, Sze-Siong; Zainol, Rosilawati; Goh, Hong Ching (PLANNING MALAYSIA, 2024)
This study evaluates the satisfaction of both international and domestic tourists within Malaysia’s oldest national park, Taman Negara Pahang, employing a quantitative methodology through a survey comprising eight distinct dimensions: amenities, service quality, natural allure, accommodation, food services, transport, recreational offerings, and expense. The researchers garnered a sample of 387 respondents via convenience sampling and analysed using frequency distribution and independent sample t-tests. Findings indicate a general satisfaction among tourists with their park visitation experience. However, the researchers identified that service quality, transport, and cost require substantial enhancements to elevate the tourist experience. While both tourist groups displayed similar satisfaction levels, international tourists reported marginally higher satisfaction across most dimensions except for recreational activities. Varying motivations, influenced by geographical origins, attribute this discrepancy to the criteria for satisfaction evaluation. The study underscores the importance of continual tourism demand for sustaining national park conservation efforts through revenue generation. The researchers anticipate that the insights derived from this research will guide enhancements in the performance of tourism products and services through diversified feedback. Marketing strategies tailored to cater to the distinct preferences of domestic and international tourists are recommended, especially for Taman Negara Pahang, which enjoys popularity among both visitor segments.